2023
DOI: 10.3390/biomedicines11071784
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Eravacycline against Carbapenemase-Producing Gram-Negative Bacilli Clinical Isolates in Central Poland

Abstract: Eravacycline is a novel antibiotic of the tetracycline class with activity against a broad spectrum of clinically significant bacteria, including multi-drug-resistant organisms. For this reason, it may be an alternative to treating critical infections of this etiology. We aimed to assess the in vitro effectiveness of eravacycline to carbapenemase-producing Gram-negative bacilli clinical isolates identified in hospitals in Łódź, Poland. We analyzed 102 strains producing KPC, MBL, OXA-48, GES, and other carbapen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Similar to our findings are the results reported by Maraki et al, who also detected higher susceptibility to tigecycline (86%) and lower to eravacycline (60%) among carbapenemresistant Enterobacterales [30]. A recent study from Poland demonstrated good in vitro susceptibility of MBL-and KPC-producing isolates to eravacycline in 59% and 73% of the isolates, respectively [53]. Our study confirmed these findings and demonstrated higher (89.5%) susceptibility to eravacycline in the KPC/OXA-48 group than that among the NDM-1/VIM-1-producers (70%).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings are the results reported by Maraki et al, who also detected higher susceptibility to tigecycline (86%) and lower to eravacycline (60%) among carbapenemresistant Enterobacterales [30]. A recent study from Poland demonstrated good in vitro susceptibility of MBL-and KPC-producing isolates to eravacycline in 59% and 73% of the isolates, respectively [53]. Our study confirmed these findings and demonstrated higher (89.5%) susceptibility to eravacycline in the KPC/OXA-48 group than that among the NDM-1/VIM-1-producers (70%).…”
Section: Discussionsupporting
confidence: 92%
“…Avibactam forms a stable and hydrolysisresistant complex with the β-lactamase molecule, causing inhibition of β-lactamases of classes A, B, and partially D (according to Ambler's classification), including β-lactamases with a highly extended spectrum of activity , as well as the chromosomal cephalosporinase AmpC (Behzadi et al, 2020). Due to the narrow indications for using eravacycline, ceftazidime/avibactam and aztreonam are the drugs of choice for bacteremia or pneumonia (Zhanel et al, 2016;Falcone et al, 2021;Sanz Herrero, 2022;Brauncajs et al, 2023). In July 2023, Mark G. Wise reported data on the evaluation of the in vitro activity of aztreonam/avibactam, a new antibiotic, against Enterobacterales isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Eravacycline is a new synthetic fluorocycline recently approved by the FDA and the EMA for the treatment of complicated intra-abdominal infections (cIAI) in adult patients [68]. It is structurally similar to tigecycline but has two unique chemical modifications that confer in vitro activity against most Gram-positive and Gram-negative organisms, including CRAB, except for P. aeruginosa [68,69]. It can be administered intravenously and orally and exerts its antibacterial activity by reversibly binding to the bacterial ribosomal 30S subunit [70].…”
Section: Eravacyclinementioning
confidence: 99%